Pelecehan Seksual terhadap Anak Melalui Media Sosial dari Prespektif Hukum Pidana dan Perlindungan Anak - Salsabila, Annisa Shafa; Prabandani, Hendra Wahanu (Neolectura, 2025)
The protection of children from sexual abuse in the digital era has become a crucial issue in Indonesia, along with the increasing access of children to social media. This study analyzes the relationship between sexual abuse of children through social media from the perspective of criminal law and child protection. In the digital era characterized by the rapid development of information technology, access to social media provides convenience for social interaction. However, this phenomenon also increases the risk of children becoming victims of sexual abuse. Data shows that more than 70% (seventy percent) of children in Indonesia have access to the internet, which makes them vulnerable to the actions of sexual predators. With the advancement of technology, sexual predators utilize digital platforms to exploit children. This research identifies various forms of abuse that occur on social media, including the sending of sexual content and requests to perform immoral acts. In addition, this analysis evaluates the effectiveness of existing laws, including the Criminal Code and the Child Protection Law, as well as challenges in implementation